Long-course versus short-course palliative cranial irradiation in brain metastases: a comparative study - Maheshwari, Guncha; Yadav, Manju Lata; Jakhar, Shankar Lal; Sharma, Neeti; Kumar, H. S.; Dhanawat, Aditya (International Journal of Advances in Medicine, 2019)
Background: Brain metastases are the most common intracranial malignancy in adults and their management poses a significant healthcare problem. Of the various options available, whole brain radiotherapy (WBRT) remains the mainstay of treatment. Nonetheless, there is a need to develop fractionation schedules for best symptom palliation and prolonged survival. This prospective study aims to compare treatment outcome in terms of overall survival in two different WBRT schedules and determine the prognostic factors affecting this outcome. Methods: Sixty previously untreated patients with symptomatic brain metastases were randomized in two arms of 30 patients each to receive WBRT. Arm A patients received 30Gy in 10 fractions (long-course) and arm B received 20Gy in 5 fractions (short-course). All patients were assessed during and after completion of WBRT at 1, 3, 6, 9 and 12 months. Results: At 12 months post WBRT, the objective response rate i.e. complete and partial response (CR+PR) was 6.67% in arm A and 13.34% in arm B (p=0.96). Both WBRT regimens showed similar survival (p=0.65). On multivariate linear regression analysis, age ≤65 years, Karnofsky performance score (KPS) ≥70 and lack of extra-cranial metastases were significantly associated with improved survival at the end of 12 months post WBRT. EORTC QLQ-C30 showed similar improvement in quality of life in both the arms (p=0.86). Conclusions: This study suggests comparable results in the two fractionation schedules. Therefore, short-course WBRT may be used as a more convenient option in favour of shorter hospital stay and lesser burden on RT machines.